Perception and Practices of Self-Medication among University Students in Lahore, Pakistan : Perception and Practices of Self-Medication - Ali, Tooba; Yaqoob, Muhammad; Hameed, Sajid; Aziz, Ghofran; Naseer, Anam; Tariq, Safina (Pakistan Journal of Health Sciences, 2023)
According to World Health Organization, self-medication is defined as the “use of over-the-counter medication to treat self-diagnosed symptoms or disorders or for the continuous and re-use of prescribed medications for recurrent diseases.” Objective: To compare the perception and practice of self-medication among medical and non-medical students at the University of Lahore, Pakistan. Methods: It is a comparative cross-sectional study with non-probability convenient sampling technique. Five hundred and eighty four students participated in this survey. The data were collected through questionnaire. Results: 98.6% of the students were self-medicating; 50.1% were medical and 49.9% were non-medical students. The frequency of medical students knowing more about the medicines they consumed needed a prescription, and self-medication is not safe to treat the illness is higher than in non-medical students. Personal knowledge was the main source and time saving was the main cause of self-medication. The frequency of medical students reading the leaflet is higher in medical than in non-medical students. The frequency of painkillers is higher in non-medical students compared to medical students. The most frequent indications for self-remedy in both groups were headache, fever, cough & common cold. Conclusions: The frequency of self-medication was high among the students of the University of Lahore. The population may be educated against the harmful effects of self-medication and authorities should monitor pharmacies that are part of the self-medication process